ChemInform Abstract: Bimetallic Oxidative Addition Involving Radical Intermediates in Nickel‐Catalyzed Alkyl—Alkyl Kumada Coupling Reactions. Issue 50 (10th December 2013) - Breitenfeld, Jan; Ruiz, Jesus; Wodrich, Matthew D.; Hu, Xile
Abstract mechanistic studies